2009
DOI: 10.1055/s-0029-1243369
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcomes in Normal Weight and Obese Women in Relation to Gestational Weight Gain: Comparison between Institute of Medicine Guidelines and Cedergren Criteria

Abstract: We compared obstetric outcomes based on gestational weight gain in normal-weight and obese women using traditional Institute of Medicine (IOM) guidelines and newly recommended Cedergren criteria. Using the New Jersey Pregnancy Risk Assessment Monitoring System (PRAMS) database and electronic birth records, perinatal outcomes were analyzed to estimate the independent effects of prepregnancy body mass index (BMI) and gestational weight gain by IOM versus Cedergren criteria. Of 9125 subjects in PRAMS database fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…In addition, another study in 2010 by Potti et al . suggested an optimal gestational weight that fell between those proposed by Cedergren and 2009 IOM . These divergences suggest that optimal ranges of weight gain during pregnancy may be population‐specific.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, another study in 2010 by Potti et al . suggested an optimal gestational weight that fell between those proposed by Cedergren and 2009 IOM . These divergences suggest that optimal ranges of weight gain during pregnancy may be population‐specific.…”
Section: Discussionmentioning
confidence: 83%
“…GWG includes fetal weight, which is the basis to calculate SGA or LGA, but GWG is more inclusive than fetal weight (e.g., placenta, amniotic fluid, water retention, fat deposits) and is easier to measure by clinicians and pregnant women than nutrition intake and energy balance. 18 Since the issuance of IOM 2009 GWG guidelines, various efforts were taken to validate or refine the guidelines, including noninferiority margin of adverse perinatal outcomes by GWG z-score, 19 increased focus on obesity or overweight women, 15, 20, 21, 22, 23 or examining trimester-specific weight gain. 24, 25 However, no prior studies have attempted to refine the guidelines by individual prepregnancy BMI unit, even in the case that GWG was considered for prepregnancy BMIs in obesity classes I, II, and III.…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study conducted in the United States has shown that maternal weight gain during pregnancy correlates with birth weight. 27 Rao et al 28 evaluated the relationship between various factors such as multiparity, pregestational overweight or obesity, advanced maternal age, prolonged gestational age and excessive gestational weight gain with the manifestation of fetal macrosomia. In that study, only excessive gestational weight gain was significantly associated with macrosomia.…”
Section: Conflict Of Interestmentioning
confidence: 99%